Novel Approach to Elucidate Human Baroreflex Regulation at the Brainstem Level: Pharmacological Testing During fMRI - Gerlach, Darius A.; Manuel, Jorge; Hoff, Alex; Kronsbein, Hendrik; Hoffmann, Fabian; Heusser, Karsten; Ehmke, Heimo; Diedrich, André; Jordan, Jens; Tank, Jens; Beissner, Florian (Frontiers in Neuroscience, 2019)
Introduction Brainstem nuclei govern the arterial baroreflex, which is crucial for heart rate and blood pressure control. Yet, brainstem function is difficult to explore in living humans and is therefore, mostly studied using animal models or postmortem human anatomy studies. We developed a methodology to identify brainstem nuclei involved in baroreflex cardiovascular control in humans by combining pharmacological baroreflex testing with functional magnetic resonance imaging. Materials and Methods In eleven healthy men, we applied eight repeated intravenous phenylephrine bolus doses of 25 µg and 75 µg followed by a saline flush using a remote-controlled injector during multiband functional MRI acquisition of the whole brain including the brainstem. Continuous finger arterial blood pressure, respiration, and ECG were monitored. fMRI data were preprocessed with a brainstem-specific pipeline and analyzed with a general linear model (GLM) to identify brainstem nuclei involved in central integration of the baroreceptor input. Results Phenylephrine elicited a pressor response followed by a baroreflex-mediated lengthening of the RR interval (25 µg: 197±15 ms; 75 µg: 221±33 ms). By combining fMRI responses during both phenylephrine doses, we identified significant signal changes in the nucleus tractus solitarii (t=5.97), caudal ventrolateral medulla (t=4.59), rostral ventrolateral medulla (t=7.11), nucleus ambiguus (t=5.6), nucleus raphe obscurus (t=6.45) and several other brainstem nuclei (p < 0.0005 FWE-corr.). Conclusions Pharmacological baroreflex testing during fMRI allows characterizing central baroreflex regulation at the level of the brainstem in humans. Baroreflex-mediated activation and deactivation patterns are consistent with previous investigations in animal models. The methodology has the potential to elucidate human physiology and mechanisms of autonomic cardiovascular disease.